ionlydothemath
New member
- Joined
- Jun 11, 2017
- Messages
- 1
I need to solve for x -
log15 (x) + log15 (x - 2) + log15 (x + 3) = 1
this is my attempt so far -
log15 (x)(x - 2)(x + 3) = 1
(x)(x - 2)(x + 3) = 15
x3 + x2 - 6x = 15
x3 + x2 - 6x - 15 = 0
I can then only manage to solve the polynomial by using this equation -
x = {q + [q2 + (r-p2)3]1/2}1/3 + {q - [q2 + (r-p2)3]1/2}1/3 + p
where:
p = -b/(3a)
q = p3 + (bc-3ad)/(6a2)
r = c/(3a)
This gives me 2.88395... which is the correct answer (i believe).
I'm just wondering if there is another way of solving the problem that I might be missing?
Any help would be much appreciated.